Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0123-001 WMC/AC/553 International 16th March, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, SPAIN. I suppose you and Adler will be arranging to get out the history of the conflict in Spain, in accordance with the resolution passed by the Joint Conference last week. I think you should do this in as much detail as you can, and then we could publish the statement in our different countries, and if it is written at all graphically I think it would make good propaganda. If the material is suitable, I will try to arrange with Mr. Bevin and the "Daily Herald" Board to have some articles put in the "Herald". I am also wondering whether you could publish anything in the way of weekly notes for speakers about the situation in Spain, pushing ahead our policy as laid down in the Joint meeting, and basing them on the latest information you have got. I am rather keen that we should give as much publicity as we can to the attempts of the Italians and Germans to exploit the situation. If you could supply us with the groundwork, we in turn would publish these notes broadcast to our Trade Unions and Trades Councils, and probably to the Labour Parties also. You might also let me know whether anything has been done about the base hospital, and as to whether in fact you are going ahead with this. With best regards, Yours sincerely, General Secretary. 292/946/11/123